Overlapping Leigh Syndrome/Myoclonic Epilepsy With Ragged Red Fibres in an Adolescent Patient With a Mitochondrial DNA A8344G Mutation - Shen, Cunzhou; Xian, Wenbiao; Zhou, Hongyan; Li, Xunhua; Liang, Xiuling; Chen, Ling (Frontiers in Neurology, 2018)
We present the case of an 16-year-old man with a family history of epilepsy who presented with acute respiratory failure, limb weakness, diabetes mellitus, sinus tachycardia, lactic acidosis, and pneumonia. He went on to develop cranial nerve palsy, myoclonus, generalised seizures, ataxia, recurrent pneumonia, and hypotension. Biochemical investigation revealed elevated lactate, pyruvate, and glucose levels. Cerebral magnetic resonance imaging revealed bilateral, symmetric, high-intensity T2-weighted signals in the thalamus, brainstem, and grey matter of the spinal cord. Histochemical analyses revealed ragged red fibres (RRF) and decreased cytochrome oxidase activity. Blood and muscle-derived DNA demonstrated a high level (95% and 96%, respectively) of the m.8344A>G mutation, while almost all of his maternal relatives (n = 17, including his mother) carried the same point mutation. The point mutation level of his mother (who had short stature, high blood-lactate levels, and epilepsy) was 77% (blood-derived DNA). Although this mutation has been identified in approximately 30 individuals with these disorders, to our knowledge, this is the first reported case of overlapping Leigh syndrome/myoclonic epilepsy with RRF in an adult patient, and the largest reported pedigree of mitochondrial DNA A8344G mutation.